RECOGNITION OF BAGH-O-BAHAR IN THE CRITICISMS OF URDU DASTAN - Samina Saif; Dr. Naseema Rehman (بازیافت, 2023)
Mir Amman's writing Bagh-o-Bahar is considered as the foundation of Urdu prose. It owns a perpetual fame in Dastani Urdu literature. This Dastan possesses a vast treasure of critique on cultural and social, character and linguistic, psychological and spiritual, historical and comparative, symbolic and metaphorical, artistic and literary references. This article tends to evaluate the critique of Bagh o Bahar and assess its value and status in Dastani literature.